Impact of the absence of opioid anesthesia on postoperative outcome indicators: a systematic review and meta-analysis - Qin, Jiarun; Zhang, Jialei; Bo, Jianing; Ma, Xiaoyan; He, Xiaofeng (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to examine the effect of opioid-free anesthesia (OFA) on postoperative outcome indicators and explore its application in thoracoscopic or laparoscopic as well as non-thoracoscopic or laparoscopic surgeries, providing a scientific basis for clinical decision-making.MethodA systematic search was conducted for clinical studies comparing OFA and opioid-based anesthesia (OBA) published from the establishment of the databases to May 2025 using databases such as PubMed, Web of Science, Embase, and Cochrane Library. The primary outcome was the incidence of postoperative nausea and vomiting (PONV). Secondary outcomes included perioperative recovery indicators, the need for postoperative emergency analgesia, postoperative pain score (VAS, NRS), and adverse reactions.ResultsA total of 3,766 relevant studies were initially identified, and 68 randomized controlled trials involving 5,426 patients were ultimately included. Compared with OBA, OFA significantly reduced the risks of PONV (RR = 0.50, 95% CI: 0.39–0.64), nausea alone (RR = 0.34, 95% CI: 0.25–0.46), vomiting alone (RR = 0.34, 95% CI: 0.25–0.46), and the need for postoperative emergency analgesia (RR = 0.61, 95% CI: 0.51–0.72). OFA was also associated with lower 24 h postoperative NRS pain scores (SMD = −0.32, 95% CI: −0.53 to −0.10). For outcomes with high heterogeneity (I2 > 75%), the systematic review showed that most studies did not find a significant reduction in postoperative VAS pain scores with OFA. However, over two-thirds of the studies have shown that OFA can improve the quality of postoperative recovery (QoR-40). Approximately half of the studies suggested that OFA may prolong extubation time, while most found no significant difference in PACU stay time.ConclusionIn summary, OFA not only significantly reduces postoperative PONV, but also lowers the demand for analgesic drugs and improves the quality of postoperative recovery. However, its effect on some postoperative recovery indicators is limited, and further high-quality studies are required to confirm these findings. OFA is expected to serve as a safe and effective anesthesia strategy to optimize the perioperative outcomes of patients.